2019
DOI: 10.1186/s12885-019-5892-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios as predictive and prognostic markers in patients with locally advanced rectal cancer treated with neoadjuvant chemoradiation

Abstract: Background A standard therapy for locally advanced rectal cancer (LARC) includes fluoropyrimidine (FP)-based neoadjuvant chemoradiation (nCRT). Previous studies have inconsistently demonstrated that baseline neutrophil- and platelet-to-lymphocyte ratios (NLR and PLR) are predictive of response to nCRT or prognostic of outcomes in LARC. Methods We reviewed patients with LARC undergoing nCRT followed by surgery from 2005 to 2013 across 8 Canadian cancer centres. Outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 47 publications
3
48
0
3
Order By: Relevance
“… 34 A clinical trial by Dudani et al reported that NLR and platelet-to-lymphocyte ratio (PLR) are two useful predictive and prognostic markers in LARC patients. 35 However, some other studies did not indicate a significant association between NLR, PLR and outcomes in LARC patients. 36 , 37 A recent meta-analysis by Jin et al indicated lymph node ratio (LNR) as an independent prognostic factor for RC patients after nCRT.…”
Section: Discussionmentioning
confidence: 93%
“… 34 A clinical trial by Dudani et al reported that NLR and platelet-to-lymphocyte ratio (PLR) are two useful predictive and prognostic markers in LARC patients. 35 However, some other studies did not indicate a significant association between NLR, PLR and outcomes in LARC patients. 36 , 37 A recent meta-analysis by Jin et al indicated lymph node ratio (LNR) as an independent prognostic factor for RC patients after nCRT.…”
Section: Discussionmentioning
confidence: 93%
“…Our study included only patients receiving preoperative CRT before surgery, and pre-CRT NLR significantly correlated with survival. Meanwhile, a Canadian multicenter study (28) with the largest effect size reported that an elevated pre-CRT NLR level is not associated with OS on both univariate and multivariate analyses. When the patient and tumor characteristics were compared according to the pre-CRT NLR level, a higher pre-CRT NLR was associated with older age, poor performance status, and lower hemoglobin level, of which age and performance status were significant prognostic factors affecting OS on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this study differed from previous studies in methodology. A common feature of previous studies was to dichotomize continuous biomarkers primitively to stratify patients into different subgroups to explore the correlations of these biomarkers with response or prognosis, and thus the cut off values of these biomarkers are various in different literature (17,(24)(25)(26)(27)(28)(31)(32)(33)(34)(35). In this study, we choose not to dichotomize these biomarkers primitively, because the forecasts of continuous variables have enormous advantages from a statistical standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that NLR, LMR, and PLR could not be used to distinguish total tumor regression from the residual disease after nCRT; while higher PLR was correlated with improved recurrence-free survival ( 31 ). Michael et al found that NLR and PLR are neither independent predictors of response nor prognostic factors in LARC patients undergoing nCRT followed by radical surgery ( 32 ). However, the data from William et al showed that baseline lower levels of LMR and higher levels of NLR and PLR were correlated with decreased OS ( 25 ).…”
Section: Discussionmentioning
confidence: 99%